Wahhabism vs. Wahhabism : Qatar challenges Saudi Arabia - James M. Dorsey (2014)
Qatar, a tiny energy-rich state in terms of territory and population, has exploded on to the world map as a major rival to the region’s behemoth, Saudi Arabia. By projecting itself through an activist foreign policy, an acclaimed and at times controversial global broadcaster, an airline that has turned it into a transportation hub and a host of mega sporting events, Qatar has sought to develop the soft power needed to compensate for its inability to ensure its security, safety and defence militarily. In doing so, it has demonstrated that size no longer necessarily is the determining factor for a state’s ability to enhance its influence and power. Its challenge to Saudi Arabia is magnified by the fact that it alongside the kingdom is the world’s only state that adheres to Wahhabism, an austere interpretation in Islam. Qatari conservatism is however everything but a mirror image of Saudi Arabia’s stark way of life with its powerful, conservative clergy, absolute gender segregation; total ban on alcohol and houses of worship for adherents of other religions, and refusal to accommodate alternative lifestyles or religious practices. Qatar’s alternative adaptation of Wahhabism coupled with its lack of an indigenous clergy and long-standing relationship with the Muslim Brotherhood, the region’s only organised opposition force, complicate its relationship with Saudi Arabia and elevate it to a potentially serious threat.